Successful management of an arteriovenous malformation with trametinib in a patient with capillary‐malformation arteriovenous malformation syndrome and cardiac compromise. Issue 2 (10th January 2022) - Nicholson, Cynthia L.; Flanagan, Siobhan; Murati, Michael; Boull, Christina; McGough, Erin; Ameduri, Rebecca; Weigel, Brenda; Maguiness, Sheilagh
Abstract: Capillary malformation‐arteriovenous malformation (CM‐AVM) syndrome is an autosomal dominant condition characterized by multifocal, noncontiguous pink patches on the skin that often have a surrounding pale halo. In some cases, an association with a fast flow, arteriovenous malformation (AVM) can be identified. Here, we describe a case report of a 16‐year‐old woman with CM‐AVM syndrome and significant cardiac compromise successfully treated with trametinib, a mitogen‐activated protein kinase (MEK) inhibitor.